Doble exilio y doble escritura en Diario a dos voces de José María y Manuel Lamana - Símini, Diego (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
An analysis of writing patterns of the two diaries composing the text Diario a dos voces. The paper shows the stylistic aspects of both authors and explores the testimonial value and literary impact of the text.